2015
DOI: 10.3390/rs70201279
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Mapping Soil Moisture of Plateau Pasture Using RADARSAT-2 Imagery

Abstract: Accurate soil moisture retrieval of a large area in high resolution is significant for plateau pasture. The object of this paper is to investigate the estimation of volumetric soil moisture in vegetated areas of plateau pasture using fully polarimetric C-band RADARSAT-2 SAR (Synthetic Aperture Radar) images. Based on the water cloud model, Chen model, and Dubois model, we proposed two developed algorithms for soil moisture retrieval and validated their performance using experimental data. We eliminated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…Our models (including SVR method) prediction error seems to be high in comparison to previous SAR/remote sensing based soil moisture prediction studies (e.g., [23][24][25][36][37][38]) and showed an overestimation of soil moisture in comparison to AWS observed values. This could be attributed to (i) the limited number of ground observed stations-with the limited number of observation stations, it is difficult to entirely characterize the spatial patterns of soil moisture over the study area, (ii) the use of soil moisture observed/simulated at 20/10 cm soil depth during model development, while microwave signals at the C-band are more sensitive to volumetric moisture to the top few centimeters of soil [81], (iii) spatial scale difference between ground observed points and satellite footprints/pixels, and (iv) sub-pixel heterogeneity of land surface conditions for lower scale analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…Our models (including SVR method) prediction error seems to be high in comparison to previous SAR/remote sensing based soil moisture prediction studies (e.g., [23][24][25][36][37][38]) and showed an overestimation of soil moisture in comparison to AWS observed values. This could be attributed to (i) the limited number of ground observed stations-with the limited number of observation stations, it is difficult to entirely characterize the spatial patterns of soil moisture over the study area, (ii) the use of soil moisture observed/simulated at 20/10 cm soil depth during model development, while microwave signals at the C-band are more sensitive to volumetric moisture to the top few centimeters of soil [81], (iii) spatial scale difference between ground observed points and satellite footprints/pixels, and (iv) sub-pixel heterogeneity of land surface conditions for lower scale analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…In fact, soil moisture content (SMC) controls the exchange of latent and sensible heat between land and atmosphere across the surface, which is the trigger of feedback mechanisms in land-atmosphere interactions [5]. Soil moisture has great importance in various applications such as natural risk assessment, hydrology, climatology, ecology, and agronomy, whereby the retrieval of spatial distribution of SMC on a large scale is an important research topic [6].…”
Section: Introductionmentioning
confidence: 99%
“…The vegetation index (NDVI) obtained from measurements of this sensor showed strong correlations with parameters related to pasture quality (PMC, with R 2 of 0.91; CP, with R 2 of 0.82) or to pasture quality degradation (PQDI, with R 2 of 0.93; NDF with R 2 of 0.84). These results are justified by the principle of NDVI, based on reflectance at the near infrared and red regions, which is strongly related to the vegetation density [47] or to the chlorophyll content, and thus, with the plant growth [48]. Serrano et al [17], Albayrak [49], and Pullanagari et al [50] also found significant relationships between spectral measurements and pasture quality parameters, which can be attributed to the absorbance of visible radiance by the existing chlorophyll in green vegetation.…”
Section: Technologies For Monitoring Soil and Pasture Variabilitymentioning
confidence: 85%